Optimalisasi Perlindungan Konsumen Digital untuk Mencegah Brainrot dalam Perspektif Tujuan Pembangunan Berkelanjutan (SDGs) 3 - Josef Purwadi; Ayu Kumala Sari Hamidi (Integralistik, 2026)
The rapid development of digital technology has given rise to the phenomenon of brainrot, referring to cognitive decline caused by excessive consumption of addictive, low-quality digital content. This phenomenon poses a serious threat to mental health, particularly among adolescents, and contradicts Sustainable Development Goal (SDG) 3 on ensuring healthy lives and well-being. This study aims to analyze the optimization of digital consumer protection in preventing the negative impacts of brainrot and to assess the relevance of SDG 3 as a normative basis for strengthening legal regulation in Indonesia. This research employs a normative juridical method using statutory and conceptual approaches, examining Law No. 8 of 1999 on Consumer Protection and Law No. 11 of 2008 on Electronic Information and Transactions, complemented by comparative analysis of international regulatory practices. The findings reveal that Indonesia’s current consumer protection framework remains focused on material losses and illegal content, thereby failing to address cognitive harm resulting from algorithmic risks of digital platforms. The main contribution of this research lies in conceptualizing brainrot as a form of juridical digital consumer harm and in positioning SDG 3 as a normative mandate for the state to require digital platforms to safeguard users’ cognitive health. This study underscores the urgency of comprehensive and preventive regulatory reform to promote a healthier and more sustainable digital ecosystem.